New heteroleptic magnesium complexes for MgO thin film application. Issue 5 (11th December 2014) - Kim, Hyo-Suk; George, Sheby Mary; Park, Bo Keun; Son, Seung Uk; Kim, Chang Gyoun; Chung, Taek-Mo
Abstract : Novel magnesium precursors for the ALD/CVD process of MgO thin films were synthesized as heteroleptic complexes. These complexes show high volatility and good thermal properties which proved to be superior to homoleptic parent complexes. Abstract : Novel heteroleptic magnesium complexes, [Mg(dmamp)(acac)]2 (1 ), [Mg(dmamp)(tmhd)]2 (2 ), [Mg(dmamp)(tfac)]2 (3 ), and [Mg(dmamp)(hfac)]2 (4 ), were successfully synthesized using dmamp and β-diketonate as ligands. The thermogravimetric analyses and volatile studies of the complexes showed that the complexes2 and4 display high volatility and thermal stability. The single crystal X-ray study of the complexes reveals that both the complexes1 and2 were crystalized in the triclinic space group and as dimers, where magnesium atoms are in the pentacoordinate state with distorted trigonal bipyramidal geometry.